Arp2/3 Complex Is Required for Auxin-Driven Cell Expansion Through Regulation of Auxin Transporter Homeostasis - García-González, Judith; Kebrlová, Štépánka; Semerák, Matěj; Lacek, Jozef; Kotannal Baby, Innu; Petrášek, Jan; Schwarzerová, Kateřina (Frontiers in Plant Science, 2020)
The Arp2/3 complex is an actin nucleator shown to be required throughout plant morphogenesis, contributing to processes such as cell expansion, tissue differentiation or cell wall assembly. A recent publication demonstrated that plants lacking functional Arp2/3 complex also present defects in auxin distribution and transport. This work shows that Arp2/3 complex subunits are predominantly expressed in the provasculature, although other plant tissues also show promoter activity (e.g., cotyledons, apical meristems, or root tip). Moreover, auxin can trigger subunit expression, indicating a role of this phytohormone in mediating the complex activity. Further investigation of the functional interaction between Arp2/3 complex and auxin signaling also reveals their cooperation in determining pavement cell shape, presumably through the role of Arp2/3 complex in the correct auxin carrier trafficking. Young seedlings of arpc5 mutants show increased auxin-triggered proteasomal degradation of DII-VENUS and altered PIN3 distribution, with higher levels of the protein in the vacuole. Closer observation of vacuolar morphology revealed the presence of a more fragmented vacuolar compartment when Arp2/3 function is abolished, hinting a generalized role of Arp2/3 complex in endomembrane function and protein trafficking.